PENERAPAN METODE PENCUCIAN DENGAN AIR MENGALIR UNTUK MENURUNKAN KADAR NITRIT PADA SARANG BURUNG WALET (Application of Washing Method under Running Water to Reduce Nitrit Level of Edible Birds Nest) - Susilo, Heru; Latif, Hadri; Ridwan, Yusuf (Jurnal Kedokteran Hewan, 2016)
This study was aimed to determine the influence of the washing method under running water on nitrite levels of edible birds nest (EBN). Total of 40 samples of EBN were divided into four groups with different washing frequency, control group without washing treatmet (P0), once, twice, and three times washing treatment (P1, P2, and P3) respectively. Each washing was performed for 30 seconds under running water. Nitrite levels assessment was carried out by spectrophotometry at 540 nm of wavelength. The results showed that the average nitrite levels of EBN in P0, P1, P2, and P3 were 93.124.40 ppm, 65.243.38 ppm, 63.603.81 ppm, and 30.872.11 ppm, respectively. The nitrit level in edible birds nest decreased significantly (P0.05) by using three times washing.